2016
DOI: 10.12659/ajcr.897671
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Diagnosis and Treatment of Serotonin Syndrome Following Administration of Methylene Blue

Abstract: Patient: Male, 67Final Diagnosis: Serotonin syndromeSymptoms: Agitation • muscular spasticity, deficient muscular control • nystygmus • sweating • tachycardiaMedication: Methylene BlueClinical Procedure: Total abdominal colectomySpecialty: AnesthesiologyObjective:Unusual clinical courseBackground:Serotonin syndrome (SS) involves serotonergic hyperactivity caused by excessive activation of 5-HT2A receptors. As the use of antidepressants increases, so does the population of patients at risk for developing this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Seventy percent of patients recover completely within 24 h, 40% of patients require admission to an intensive care unit, and only 25% of patients require endotracheal intubation [91]. In addition to stopping serotonergic medications, the treatment of SS in humans has consisted primarily of supportive care, including the administration of benzodiazepines [1,10,92,93,94]. Given that life-threatening manifestations of SS such as rigidity and hyperthermia seem to result only from stimulation of 5-HT 2A receptors [20], it would follow that directed therapy for this disease would target this particular receptor.…”
Section: Receptor-targeted Therapy For Serotonin Syndromementioning
confidence: 99%
“…Seventy percent of patients recover completely within 24 h, 40% of patients require admission to an intensive care unit, and only 25% of patients require endotracheal intubation [91]. In addition to stopping serotonergic medications, the treatment of SS in humans has consisted primarily of supportive care, including the administration of benzodiazepines [1,10,92,93,94]. Given that life-threatening manifestations of SS such as rigidity and hyperthermia seem to result only from stimulation of 5-HT 2A receptors [20], it would follow that directed therapy for this disease would target this particular receptor.…”
Section: Receptor-targeted Therapy For Serotonin Syndromementioning
confidence: 99%
“…However, this condition may be precipitated by adding a single dose of MB. The Food and Drug Administration (FDA) recommends for patients who are at risk to be exposed to MB to stop taking serotonergic agents at least 2 weeks prior to its potential administration [25,26].…”
Section: Methylene Bluementioning
confidence: 99%
“…Although MB has an excellent curative effect in the treatment of methemoglobin, it may lead to Heinz body anemia, morphological changes of red blood cells and necrotic edema if the dosage of methylene blue is too high [7]. It can produce a burning sensation through oral intake, and may cause nausea, vomiting, sweating, mental disorder and methemoglobinemia, etc [8]. At present, several countries or institutions, including USA, EU and Japan, have formulated for the detection of methylene blue residues in aquatic products.…”
Section: Introductionmentioning
confidence: 99%
“…NRS was pretreated using epichlorohydrin and concentrated H 2 SO 4 in various impregnation ratios to produce modified NRS called NRSEA. The results of MB adsorption ability test onto NRSEA showed that the adsorption capacity increased with increasing pH (within the pH range of [7][8][9][10][11][12] and decreased afterwards, the optimum initial MB concentration reached at 800 mg/L, and the equilibrium state was achieved at 120 min of contact time. Enhanced methylene blue removal from aqueous solution using modified rubber seed (Hevea brasiliensis).…”
Section: Introductionmentioning
confidence: 99%